A history of engineering in classical and medieval times - Hill, Donald Routledge (Croom Helm, 1984)
This is a rather dry accounting of some of the key technological accomplishments in the given era. Although the title says "history," the book is organized by subject rather than chronology. Part One focuses on civil engineering: irrigation, dams, bridges, surveying, etc. Part Two deals with mechanical engineering: water-raising devices, mills, etc. And Part Three looks at "fine technology:" instruments, automata, and particularly clocks.